Effect of Nano-TiO2 Addition to Dexlite Diesel Fuel on Gas Emissions - Dharmawan, Aditya; Pasha, Pangeran Rafli; Putra, Restu Ramadhani Pratama (Fakultas Teknologi Mineral, Universitas Pembangunan Nasional (UPN), 2024)
The increase in the number of diesel vehicles in Indonesia causes an increase in diesel fuel energy demand, so that the use of fuel must be managed as effectively and efficiently as possible. In this study, the addition of TiO2 nanoparticle additives to Dexlite carried out using the ultrasonic bath method. Each batch of synthesis carried out with a capacity of 200 mL for 20 minutes, with variations in Nano-TiO2 loading on Dexlite from 0 mg/L to 200 mg/L. Then tested for physical properties such as density, viscosity, flash point and heating value. They were also tested for emission tests. It was found that the physical properties such as density, viscosity, flash point and heating value of Dexlite-Nano TiO2 did not change significantly. For the emission test, the hydrocarbon emission test results showed a 74% decrease, NOx emission test results showed a 29% decrease, CO emission test results showed a 37% decrease, CO2 emission test results showed a 24% increase. The decrease in NOx achieved by lowering the peak flame temperature after Nano-TiO2 added. The decrease in hydrocarbons, decrease in CO and increase in CO2 emissions achieved by a higher degree of complete combustion, from the O2 supplied by Nano-TiO2.